Combined experimental and computational investigation of cavitation evolution and excited pressure fluctuation in a convergent–divergent channel. (June 2015) - Chen, Guanghao; Wang, Guoyu; Hu, Changli; Huang, Biao; Gao, Yuan; Zhang, Mindi
Highlights: Sheet/cloud cavitation development process is divided into three main stages. Pressure fluctuations are found to be highly related with cavitation behaviors. The acceleration due to the changes in the cavity volume is analyzed. Abstract: The objective of this paper is to investigate the cavitation evolution and excited pressure fluctuation in unsteady sheet/cloud cavitating flows in a convergent–divergent channel using a combination of experimental and computational studies. In the experiments, a simultaneous sampling technique is used to synchronize the cavitation images with wall-pressure signals. The computations are based on the Navier–Stokes equations solved with a mass transfer cavitation model and a modified RNG k – ε turbulence model. The experimental results indicate that, for non-cavitating flow, neither significant fluctuation nor periodic fluctuation can be observed. However, in the case of sheet/cloud cavitating conditions, significant quasi-periodic pressure fluctuations are captured in the entire cavitation area. The numerically predicted unsteady sheet/cloud cavitation behaviors agree well with the experimental results; both the experimental and computational results indicate that a typical quasi-periodic sheet/cloud cavitation development process can be divided into three main stages: (1) the growth of the attached cavity, (2) shedding of the attached cavity, and (3) growth and collapse of the detached cavities. The quasi-periodic pressure fluctuations in sheet/cloud cavitation are found to be highly related with the time evolution of the cavitation behaviors. The acceleration due to the changes in the cavity volume is found to be the main source of the excited pressure fluctuations. The pressure signal decreases in the middle of the growing process of the attached cavity and the detached cavity. Next, the pressure signal increases and reaches a peak with the collapse of large detached cavity near transducer 4#.